An efficient method for optimizing the unsteady heat and mass transport features for convective drying of two porous moist objects in a channel - Selimefendigil, Fatih; Coban, Seda Ozcan; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2021)
In the present study, an efficient methodology is proposed for optimizing the convective drying performance of multiple porous moist objects in a channel. As the first step of the method, a PDE constraint optimization routine is utilized to obtain the optimum values of distance between the objects for maximizing the transfer rates while in the second part, unsteady coupled field equations for the channel and porous moist object domains are invoked for convective drying of multiple objects for the optimum spacing values. Finite element method is used for the numerical simulations. It was observed that the recirculation zones established behind the rectangular objects are profoundly affected with the distance between the objects. There is 12.5 % variation in the average Nu for the first block with varying the horizontal distance between the objects. The effects of vertical spacing on the average Nu is profound for the second object. while up to 80 % enhancement in the average Nu is obtained when the value is changed from sy = 0 to sy = 1.5hp. However, the optimum values of the distance that maximize the heat transfer are obtained as sx = 1.1hp and sy = 1.931hp for the horizontal distance and vertical distance. At this optimum values of parameters, reduction in the moisture content becomes 33.4 % and 98.015 % for drying times at 1000 s and 5000 s. These values are also checked with the parametric unsteady coupled field equations for the porous moist objects which shows the improved time dependent drying features for the two blocks at the optimum points.
Keywords: Porous moist; Optimization; Convective drying; Unsteady CFD; Multiple objects